Total Farm Revenue Compared to the Living Income Benchmark for the Koutiala Region - Wageningen University & Research (International Food Policy Research Institute, 2020)
The living income benchmark for a reference household (18,9 Adult Male Equivalent (AME)) was calculated based on expert knowledge and common prices. It includes the minimum cost for a nutritious diet, housing, health care, and decent housing. Guidelines were provided by Plant Production Systems, Wageningen University. The total farm income of farms was calculated, including income from crop and livestock activities and off-farm income. This income was compared to the living income benchmark.